Software Development in Colombia: A Legal Approach - Munar, Lainiver Mendoza (Law, State and Telecommunications Review, 2018)
Purpose ”“ In recent years, Colombia has been a very active country in the region, supporting the innovation and technology sector. The Ministry of Information and Communication Technologies (MINTIC) has implemented various programs, plans and strategies that from the national government seek to improve innovation and technology, within innovation and technology is the development of software, which as a construction of the human intellect deal with the need to be protected by the intellectual property regulations, specifically by the copyright laws for the Colombian case. Plans such as Live Digital in Colombia address the need of the country to be at the forefront of technology and seek the inclusion of society not only in the management of information technologies, but also in the creation, construction and development of these technologies, which promotes several public policies such as employment generation and poverty reduction. This describes the state of the art of the existing software legislation in Colombia. Methodology ”“ It is important to determine, within the Colombian legal system, the relevant regulations that regulate intellectual property in relation to the industry that develops software, for which purpose this research is carried out, followed by the study of the software development industry in Colombia, and the identification of regulations that exist on the matter. Findings ”“ It was possible to condense the state of the art in the legal field of software within the category of Copyrights in Colombia conceived, from the legal perspective, as a set of products such as computer program, the program description and the auxiliary material. Practical implications ”“ By carrying out this research, it has been possible to demonstrate the status of the software development regulations in Santiago de Cali and to propose solutions to the existing risks in the matter, making software developers to self-manage their intellectual property. Originality ”“ This article is useful for microenterprises and software development companies, as it offers an alternative instrument to protect intellectual property.